INTROVERT SENIOR HIGH SCHOOL STUDENTS’ CRITICAL THINKING IN WRITING ANALYTICAL EXPOSITION TEXT - Muhammad Hasan Affandi (STAIN Sultan Abdurrahman Kepulauan Riau, 2021)
This study was carried out to categorize and describe the six aspects of critical thinking in writing analytical exposition text activity toward the introvert senior high school students at the eleventh grade. The aspects were focus, supporting reason, reasoning, organization, convention and integration. The research design was a qualitative descriptive research. This study involved 3 introvert students who have the highest score in selecting the introvert subjects’ personality from eleventh grade. The data were divided by two, data for selecting the subject and data for categorizing and describing the critical thinking in writing. First, the data was obtained from questionnaire of MBTI, observation and interview. Second, data was obtained from writing test and interview. The findings in writing analytical exposition text that were assessed toward scoring rubric from (Finken & Ennis, 1993) that subject 1 and 2 have high critical thinking category. Then, subject 3 has a very high critical thinking category. Every subject has good capacity in six aspects, but the subject 1 and 2 were strong in focus aspect. Subject 3 was strong in focus and reasoning. The subjects were lack in convention and integration aspects.